2013
DOI: 10.1186/1757-7241-21-9
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guidelines and protocols in the prehospital and emergency care setting: a systematic review

Abstract: A gap between guidelines or protocols and clinical practice often exists, which may result in patients not receiving appropriate care. Therefore, the objectives of this systematic review were (1) to give an overview of professionals’ adherence to (inter)national guidelines and protocols in the emergency medical dispatch, prehospital and emergency department (ED) settings, and (2) to explore which factors influencing adherence were described in studies reporting on adherence. PubMed (including MEDLINE), CINAHL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 76 publications
(99 reference statements)
0
92
0
3
Order By: Relevance
“…This makes it difficult to access help for people who need immediate medical intervention. For each patient, taken to an emergency department, in accordance with current guidelines, it is decided whether the patient requires emergency diagnostics, hospitalization and surgery on an ad hoc basis or supply within the emergency department of further diagnosis and therapy [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…This makes it difficult to access help for people who need immediate medical intervention. For each patient, taken to an emergency department, in accordance with current guidelines, it is decided whether the patient requires emergency diagnostics, hospitalization and surgery on an ad hoc basis or supply within the emergency department of further diagnosis and therapy [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Estos niveles de adherencia y su variabilidad no son diferentes de lo publicado internacionalmente respecto de la adherencia a recomendaciones en distintas áreas clínicas 19,20 . Esta similitud con otros estudios sumada a la concordancia satisfactoria en la auditoria "doble" realizada a una submuestra de los registros apoya la confiabilidad en las mediciones de adherencia realizadas en el estudio.…”
Section: Principales Hallazgosunclassified
“…Requiring all EMS providers in North Carolina to follow the protocols, procedures, policies, and other relevant sections in the NCCEP document ensures a minimum baseline level of care and helps standardize prehospital care throughout the state. It has been shown that standardizing patient care reduces variation in clinical practice [2][3][4]. This is particularly important in North Carolina because many providers work in multiple EMS agencies throughout the state [5].…”
Section: Standardization Of Carementioning
confidence: 99%
“…Protocolized patient care has been shown to lead to better patient outcomes [3,4,10,11]. As such, the EMS Protocols section of the NCCEP document is perhaps the most important part of the document, and it contains 102 protocols.…”
Section: Ems Protocolsmentioning
confidence: 99%